Rural areas of Tropical Africa through school geography : from representations to space symbolic system - (:unkn) unknown (My University, 2012)
The rural areas of Tropical Africa are used by the geography applied at school to show misery and misfortune or to illustrate the diversity of the rural landscapes in the world and the dichotomy between North and South. Our thought falls under a postcolonial approach since it is a question of tracking the representations still anchored in colonial mythology and understanding their mechanism of inertia. The study of the school geography textbooks will enable us to enlighten the presence of exotico-colonial representations of the rural areas of Tropical Africa so that we can analyze them. The geography textbooks are the witnesses of a collective memory and shared representations. Their impact on the pupils and the teachers is considerable. These three actors, who make the class, form a representational and discursive community. The way knowledge is built, together with the importance of representations in the didactic process, will lead us to establish how the vision and the way one talks about a territory - even as far from us as Tropical Africa - are shaped. This vision and the way one talks about a territory is part of the development of space symbolic system. This concept can be defined like a superstructure through which the individuals and the societies develop their connections to the world, that is to say their geographicity, thus creating their own notions of territory, identity and otherness. Starting from representations, this concept allows us to observe the impact on the territories and to study their phenomenological and material dimensions, in fine to apprehend the Tropical Africa, its complexity and its movement.
Keywords: African Research